PTU-014 The Use Of Kinematic Analysis Of Bile Duct Cannulation As A Means Of Objectively Assessing Endoscopic Skill At Ercp. (9th June 2014) - Ralphs, SJL; North, O; Ristic, M; Taylor-Robinson, SD
Abstract : Introduction: Training in ERCP has become more challenging due to a reduction in diagnostic cases following the introduction of MRCP. There is a need to explore options to assist with basic training and the assessment of competency. There are currently no validated objective tools for this purpose. Simulators have been shown to enhance surgical skill and some there is some evidence to suggest that they can assist training in ERCP. 1 Kinematics, the study of motion, has been used in the objective assessment of surgical skill and endoscopic skill during colonoscopy on simulators but no studies have been done on ERCP. 2 Methods: 23 candidates perform bile duct cannulation on a modified ERCP simulator. Endoscopic experience ranged from complete novices to HPB consultants. Radiofrequency sensors were attached to the duodenoscope tip and catheter, and the procedures were videoed. Six parameters were measured from a starting point at the pylorus until bile duct cannulation was achieved. These included mean speed, total distance travelled, trajectory corrections, time to cannulation, time spent planning and number of papilla contacts. A performance score was calculated so that, with the exception of mean speed, a decrease in each parameter equated to an exponentially higher score, equating to greater skill. Results: Kinematic data showed that HPB consultants performed better than other participants at all 6 measures used to calculate the objective performance score. The greatest difference noted was for distance travelled (mean 3976 mm v 720 mm for novices and HPB consultants respectively) and procedure time (318s v 50s for the same two groups). The overall objective performance scores attained by subjects correlated well with their level of experience, and produced significant differences between the three least experienced groups (p < 0.05). The mean performance scores were; HPB consultants: 18.9 (n = 5), HPB trainees: 17.5 (n = 5), general gastroenterology trainees: 13.0 (n = 7), novices: 11.1 (n = 6). Conclusion: Kinematic analysis of a simulated bile duct cannulation enables the endoscopist's skill to be measured objectively. This method could be used to assist with the training and assessment of this advanced endoscopic procedure. References: Lim BS, Leung JW, Lee J, Yen D, Beckett L, Tancredi D, Leung FW. Effect of ERCP mechanical simulator (EMS) practice on trainees' ERCP performance in the early learning period: US multicenter randomized controlled trial. Am J Gastroenterol . 2011 Feb;106(2):300–6. Obstein KL, Patil VD, Jayender J, San José Estépar R, Spofford IS, Lengyel BI, Vosburgh KG, Thompson CC. Evaluation of colonoscopy technical skill levels by use of an objective kinematic-based system. Gastrointest Endosc . 2011 Feb;73(2):315-21 Disclosure of Interest: None Declared.